1999
DOI: 10.1007/bf03343601
|View full text |Cite
|
Sign up to set email alerts
|

Event-related brain potentials in male hypogonadism

Abstract: Several studies based on psychometric tests have determined an impairment of cognitive functions in patients with androgen deficiency. However, little is known about event-related potentials (ERPs) alterations in male hypogonadism. We investigated alterations of ERP in male hypogonadism before and 3 months after gonadotropin treatment. ERPs were elicited in 20 untreated male patients with idiopathic hypogonadotropic hypogonadism (IHH) (mean age: 21.1+/-1.4 years) and in a group of 30 male controls with compara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
1
10
0
3
Order By: Relevance
“…Similar results have been found in obese children with leptin gene mutations who have normal BP despite early-onset morbid obesity and many other features of the metabolic syndrome, including insulin resistance and dyslipidemia (19). These children had decreased rather than increased SNS activity as well as postural hypotension and attenuated RAAS responses to upright posture (19).…”
Section: Insulin Resistancesupporting
confidence: 70%
“…Similar results have been found in obese children with leptin gene mutations who have normal BP despite early-onset morbid obesity and many other features of the metabolic syndrome, including insulin resistance and dyslipidemia (19). These children had decreased rather than increased SNS activity as well as postural hypotension and attenuated RAAS responses to upright posture (19).…”
Section: Insulin Resistancesupporting
confidence: 70%
“…At baseline, before leptin replacement, patient A had clinical features of hypogonadism, as previously reported (10). His baseline measurements of testosterone and free testosterone were below the normal range for his age (10).…”
Section: Resultsmentioning
confidence: 51%
“…We have previously demonstrated that genetically based leptin deficiency due to a nonconservative missense leptin gene mutation (Cys-to-Thr in codon 105) in a highly consanguineous extended Turkish pedigree is associated with morbid obesity and hypogonadism (7,10). We prospectively studied the effects of leptin replacement therapy with recombinant methionyl human leptin (r-metHuLeptin) in three adult homozygous patients from this family who are the only three adult leptin-naive individuals identified in the world so far.…”
mentioning
confidence: 99%
“…Congenital complete leptin deficiency (3)(4)(5) or acute hypoleptinemia to Ͻ1 ng͞ml in leptinreplete humans induces changes in reproductive, thyroid, and IGF axes (10) and immune function (12), whereas increasing serum P value for nonparametric ANOVA across the three conditions. * , P Ͻ 0.05 by one-way ANOVA; †, P Ͻ 0.05 for fed vs. fasting ϩ placebo; ‡, P Ͻ 0.05 for fed vs. fasting ϩ r-metHuLeptin.…”
Section: Discussionmentioning
confidence: 99%